Oazy podatkowe w procesach globalizacji gospodarki światowej - Jankowiak, Anna (Offshore Financial Centres in the Preocess of World's Economy Globalization, 2008)
For many years the offshore financial centres are present in world's economy. New technologies, Internet and most important - globalization, are responsible for the increasing number of international transaction being operate by offshore financial centres. Many companies to avoid taxes are transmitting their businesses to tax heavens. The offshore financial centres are becoming more and more popular in world's economy and international relationships.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2008; Nr 12, s. 89-98